To Preserve or Not to Preserve the Orbit in Paranasal Sinus Neoplasms: A Meta-Analysis - Reyes, Camilo (J Neurol Surg B Skull Base, 2014)
Context The effect on survival of orbital evisceration on patients with paranasal sinus neoplasms has not been well established. Objective To review systematically the available literature concerning survival in patients who undergo surgery for paranasal sinus neoplasm with and without preservation of the eye. Data Source A retrospective meta-analysis of English and non-English articles using Medline and the Cochrane database. Eligibility Criteria Studies analyzing 5-year survival rates in patients who had orbital evisceration compared with orbital preservation for the treatment of paranasal sinus neoplasms were included in the final analysis. Data Extraction Independent review by two authors using predefined data fields. Data Synthesis A meta-analysis of four articles involving 443 patients was performed using the DerSimonian-Laird random-effects method. Results Our analysis revealed a total effect size of 0.964 in favor of preservation of the eye; however, these results are not robust, having a true effect size anywhere from 0.785 to 1.142 with a 95% confidence interval. Limitations Only retrospective observational studies were included because a prospective randomized study cannot be performed in this population. Conclusion Our study supports the notion that in select patients preservation of the eye may yield a different outcome when compared with orbital evisceration.